2016
DOI: 10.1038/bcj.2016.65
|View full text |Cite
|
Sign up to set email alerts
|

Evolving changes in disease biomarkers and risk of early progression in smoldering multiple myeloma

Abstract: We studied 190 patients with smoldering multiple myeloma (SMM) at our institution between 1973 and 2014. Evolving change in monoclonal protein level (eMP) was defined as ⩾10% increase in serum monoclonal protein (M) and/or immunoglobulin (Ig) (M/Ig) within the first 6 months of diagnosis (only if M-protein ⩾3 g/dl) and/or ⩾25% increase in M/Ig within the first 12 months, with a minimum required increase of 0.5 g/dl in M-protein and/or 500 mg/dl in Ig. Evolving change in hemoglobin (eHb) was defined as ⩾0.5 g/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
51
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 21 publications
2
51
2
Order By: Relevance
“…Three studies have elaborated on the importance of biomarkers evolving during follow-up [26][27][28]. Evolving changes in M-protein and hemoglobin levels and evolving differences The safety analysis population included patients who were randomized, received at least one dose of study drug, and contributed any safety data after the start of study treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies have elaborated on the importance of biomarkers evolving during follow-up [26][27][28]. Evolving changes in M-protein and hemoglobin levels and evolving differences The safety analysis population included patients who were randomized, received at least one dose of study drug, and contributed any safety data after the start of study treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Median time from recognition of evolving type to progression into symptomatic multiple myeloma was 1.1 years and progression rate at 3 years was 71%. Ravi et al showed the added value of evolving change in biomarkers for classifying patients with more aggressive disease biology 8 . They described a new model by factoring in an evolving pattern in M-protein burden and hemoglobin to identify a subgroup of SMM patients at higher risk of early progression to symptomatic disease within the first 2 years of diagnosis.…”
mentioning
confidence: 99%
“…Competing risk survival analysis methods were used to identify the risk of progression in the subjects with different numbers of risk factors, where death was treated as a competing risk event. Final results were compared between original 4 and evolving-change 8 Mayo clinic risk stratification models utilizing a generalized McNemar’s test of symmetry to determine if the two methods agreed. The data cutoff was August 3, 2018.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several risk-stratification systems have been developed to identify patients with SMM at the highest risk of progression, primarily based on tumor burden and elimination of normal plasma cells by the malignant clone (Table 1). 2,[9][10][11][12][13][14][15][16][17] More recently, these models have been revised to account for the revised definition of SMM, but the limitations of the risk-stratification systems do elevate the risk that many patients who may have never progressed will be subjected to potentially toxic treatments. One can certainly reduce this risk by taking the subgroup of patients identified to be at the highest risk of progression in these models.…”
mentioning
confidence: 99%